An English Teacher's Perception Of The Implementation Of The Independent Curriculum In Every School - Arfandi Waruwu (Sintaksis : Publikasi Para ahli Bahasa dan Sastra Inggris, 2024)
Curriculum is an important part of education systems around the world. The curriculum regulates learning process activities to maximize educational goals, functioning as a unit or guideline. Student learning outcomes in the daily learning process are one aspect that can have an impact on curriculum adjustments. Interviewing English teachers about the implementation of the Merdeka Curriculum in the classroom provided a number of insights. Educators share their thoughts on the difficulties in implementing an autonomous curriculum. because the facilities or different learning resources are not sufficient. They emphasize how the Merdeka Curriculum can help students learn English more effectively by encouraging active participation in class, fostering critical thinking, and increasing language proficiency. The student-centered curriculum philosophy was awarded